Odpowiedzi

2009-11-10T15:01:26+01:00
A) (x+1)(x+2)(x+3)= (x² + 2x +x +2)(x+3)= x³ + 3x² +2x³+6x+x²+3x+2x+6= 3x³ +4x²+11x+6
b) (x-2)(x+5)(2x-1)= (x²+5x-2x-10)(2x-1) = 2x³-x²+10x²-5x-4x²+2x-20x+10=2x³+5x²-23x+10
c)(x-4)(x+1)²= (x-4)(x²+2x+1)= x³+2x²+x-4x²-8x-4=x³-2x²-7x-4
d)(2x-3)²(x+2)=(4x²-12x+9)(x+2)= 4x³+8x²-12x²-24+9x+18=4x³-4x²+9x-6
nie jestem pewna, czy dobrze
Najlepsza Odpowiedź!
2009-11-10T15:06:21+01:00
A) (x+1)(x+2)(x+3)=(x²+2x+x+2)(x+3)=x³+3x²+2x²+6x+x²+3x+2x+6=x³+6x²+11x+6

b)(x-2)(x+5)(2x-1)=(x²+5x-2x-10)(2x-1)=2x³-x²+10x²-5x-4x²+2x-20x+10=2x³+5x²-23x+10

c)(x-4)(x+1)²=(x-4)(x²+2x+1)=x³+2x²+x-4x²-8x-4=x³-2x²-7x-4

d)(2x-3)²(x+2)=((2x)²-2*2x*3+3²)(x+2)=(4x²-12x+9)(x+2)=4x³+8x²-12x²-24x+9x+18=4x³-4x²-15x+18